What helps or hinders midwives to implement physical activity guidelines for obese pregnant women? A questionnaire survey using the Theoretical Domains Framework. (June 2017) - McParlin, Catherine; Bell, Ruth; Robson, Stephen C.; Muirhead, Colin R.; Araújo-Soares, Vera
Abstract: Objective: to investigate barriers and facilitators to physical activity (PA) guideline implementation for midwives when advising obese pregnant women. Design: a cross-sectional, self-completion, anonymous questionnaire was designed using the Theoretical Domains Framework. this framework was developed to evaluate the implementation of guidelines by health care professionals. A total of 40 questions were included. These were informed by previous research on pregnant women's and midwives views, knowledge and attitudes to PA, and supported by national evidence based guidelines. Demographic information and free text comments were also collected. Setting: three diverse NHS Trusts in the North East of England. Participants: all midwives employed by two hospital Trusts and the community midwives from the third Trust ( n =375) were invited to participate. Measurements: mean domain scores were calculated. Factor and regression analysis were performed to describe which theoretical domains may be influencing practice. Free text comments were analysed thematically. Findings: 192 (53%) questionnaires were returned. Mean domain scores were highest for social professional role and knowledge, and lowest for skills, beliefs about capabilities and behaviour regulation. Regression analysis indicated that skills and memory/attention/decision domains had a statistically significant influence on midwives discussing PA with obese pregnant women and advising them accordingly. Midwives comments indicated that they felt it was part of their role to discuss PA with all pregnant women but felt they lacked the skills and resources to do so effectively. Key conclusions: midwives seem to have the necessary knowledge about the need/importance of PA advice for obese women and believe it is part of their role, but perceive they lack necessary skills and resources, and do not plan or prioritise the discussion regarding PA with obese pregnant woman. Implications for practice: designing interventions that improve skills, promote routine enquiry regarding PA and provide resources (eg. information, referral pathways) may help improve midwives' PA advice. Highlights: Midwives see it as their role to discuss physical activity with obese women. They feel knowledgeable but lack communication skills. Midwives do not plan or prioritise a discussion around physical activity. Lack of time and resources influence midwives behaviour. Training and routine enquiry may make the discussion more likely.